Measures of emotion regulation: Convergence and psychometric properties of the difficulties in emotion regulation scale and emotion regulation questionnaire. Issue 2 (3rd July 2021) - Sörman, Karolina; Garke, Maria Å.; Isacsson, Nils H.; Jangard, Simon; Bjureberg, Johan; Hellner, Clara; Sinha, Rajita; Jayaram‐Lindström, Nitya
Abstract: O bjective: Investigating unique and shared aspects of measures of emotion regulation (ER) advances our understanding of ER as a multidimensional construct. This study aimed to investigate psychometric properties of three ER‐measures: Difficulties in Emotion Regulation Scale (DERS‐36), the abbreviated version DERS‐16, and Emotion Regulation Questionnaire (ERQ). Methods: In a community sample ( N = 843; 56% females) we investigated their internal consistency, factor structure, convergence, and association with symptoms of depression, anxiety, stress and substance abuse. R esults: The proposed factor structures of the DERS‐16 and the ERQ demonstrated an adequate fit. There were moderate correlations between the two DERS versions (36 and 16) and ERQ subscales Reappraisal and Suppression. Total scores of DERS‐36 and DERS‐16 demonstrated preferential associations with depression and anxiety. Corresponding associations between ERQ subscales and psychiatric symptoms were weak. C onclusion: The results indicate that DERS‐16 could be useful as an alternative, easily administered measure of ER difficulties.